2019
DOI: 10.1155/2019/3120391
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 Attenuates LPS-Induced Inflammatory Response in Macrophages via NF-κB Signaling Pathway

Abstract: Methyltransferase-like 3 (METTL3), an RNA N6-methyladenosine (m6A) methyltransferase, is essential for the m6A mRNA modification. As a key enzyme of m6A methylation modification, METTL3 has been implicated in immune and inflammation regulation. However, little is known of the role and underlying mechanism of METTL3 in rheumatoid arthritis (RA). The aim of the present study is to elucidate the function and potential mechanism of METTL3 in RA pathogenesis. We used quantitative real-time polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
123
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(127 citation statements)
references
References 34 publications
4
123
0
Order By: Relevance
“…The reason of downregulated m6A regulators in RA compared with CON may be the environmental, infectious, and genetic factor, as well as some RA risk factors (unbalance of adaptive and innate immune). Recently, Wang and colleagues have investigated the expression of METTL3, FTO, ALKBH5, METTL14, and YTHDF2 in peripheral blood mononuclear cell from RA patients and reported conflicting results in which only METTL3 was obviously upregulated in RA [27]. The reasons for these outcomes are probably due to differences in cell type and the disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…The reason of downregulated m6A regulators in RA compared with CON may be the environmental, infectious, and genetic factor, as well as some RA risk factors (unbalance of adaptive and innate immune). Recently, Wang and colleagues have investigated the expression of METTL3, FTO, ALKBH5, METTL14, and YTHDF2 in peripheral blood mononuclear cell from RA patients and reported conflicting results in which only METTL3 was obviously upregulated in RA [27]. The reasons for these outcomes are probably due to differences in cell type and the disease duration.…”
Section: Discussionmentioning
confidence: 99%
“…An integrative study performed by Wang J. et al (2019) analyzing the transcriptome-wide m 6 A methylome enriched by chemotherapy in OS stem cells (OSCs) has revealed that several m 6 A-related enzymes (METTL3, METTL14, FTO, ALKBH5) were altered in OS cells compared with noncancerous counterparts. The aberrantly expressed genes were associated with pluripotency regulation of the OSCs ( Wang J. et al, 2019 ).…”
Section: Roles Of M 6 a In Musculoskeletal Disordementioning
confidence: 99%
“…An integrative study performed by Wang J. et al (2019) analyzing the transcriptome-wide m 6 A methylome enriched by chemotherapy in OS stem cells (OSCs) has revealed that several m 6 A-related enzymes (METTL3, METTL14, FTO, ALKBH5) were altered in OS cells compared with noncancerous counterparts. The aberrantly expressed genes were associated with pluripotency regulation of the OSCs ( Wang J. et al, 2019 ). Further, it has been shown that lncRNA plasmacytoma variant translocation 1 (PVT1) transcript was upregulated because of m 6 A methylation decrease mediated by ALKBH5, which reduced the binding of reader protein YTHDF2 in PVT1, subsequently lessening the degradation of PVT1 and promoting tumorigenesis of OS ( Chen et al, 2020 ).…”
Section: Roles Of M 6 a In Musculoskeletal Disordementioning
confidence: 99%
See 1 more Smart Citation
“…Among these, METTL3 showed the most obvious difference between normal cells and DON-treated cells. METTL3, as a key enzyme of m 6 A methylation modi cation, can attenuate LPS induced in ammatory response in macrophages through NF-κB signaling pathway [48]. METTL3 knockdown inhibits osteoblast differentiation and activates the in ammatory response by regulating MAPK signaling in LPS-induced in ammation [49].…”
Section: Discussionmentioning
confidence: 99%